IMPLIKASI LANDASAN PENDIDIKAN TERHADAP KURIKULUM - Fahruddin; Habib Anwar Al- Anshari (Didaktik : Jurnal Ilmiah PGSD STKIP Subang, 2026)
This study presents a comprehensive analysis of the urgency of the foundation of education in formulating an adaptive and relevant curriculum in Indonesia. The main problem identified is the frequent failure of education policy implementation due to the weak underlying philosophical, sociological, psychological, and technological foundations. The phenomenon of "changing ministers, changing curriculums" shows orientation instability that has an impact on the confusion of practitioners in the field. The importance of this paper lies in the effort to synchronize the ideal ideals of national education with the reality of community needs and dynamic global challenges. The methodology used is a descriptive qualitative literature study through the Systematic Literature Review (SLR) approach to synthesize data from various scientific literature and national statistical reports. The results found show that the philosophical foundation of Pancasila provides an ideological direction, the psychological foundation ensures the suitability of the material with the development phase of students, the sociological foundation integrates local wisdom to prevent cultural alienation, and the foundation of science and technology encourages digital transformation. Statistical findings confirm that a flexible and focused curriculum on essential materials, such as the Independent Curriculum, is able to mitigate the impact of learning loss significantly by increasing measurable literacy and numeracy scores. This report provides in-depth insights for policymakers and educators to strengthen the orientation of the implementation of a solid foundation-based curriculum.